2015
DOI: 10.1002/acr.22586
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity Measured by Accelerometer, Knee Joint Abnormalities, and Cartilage T2 Measurements Obtained From 3T Magnetic Resonance Imaging: Data From the Osteoarthritis Initiative

Abstract: Objective To study the cross-sectional association between physical activity measured with an accelerometer, structural knee abnormalities and cartilage T2-values assessed with 3T MRI. Methods We included 274 subjects from the Osteoarthritis Initiative cohort without definite radiographic osteoarthritis (KL 0 and 1) and at most mild pain, stiffness and functional limitation in the study knee (WOMAC 0–1), which had not limited their activity due to knee pain. Physical activity was measured over seven days wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 47 publications
1
27
0
4
Order By: Relevance
“…Preventative efforts such as weight reduction(17,43) and various levels of exercise(16,44) may decrease risk for OA progression and may be advised after assessing an individual’s long term risk for OA. One study found that a weight loss of 5% body weight over 30 months decreased the risk of incident radiographic knee OA(45); another study suggested that moderate exercise may be a “good treatment” for subjects at high risk for OA(46), and a meta-analysis showed that long term weight loss is increased when diet and physical activity are combined(47).…”
Section: Discussionmentioning
confidence: 99%
“…Preventative efforts such as weight reduction(17,43) and various levels of exercise(16,44) may decrease risk for OA progression and may be advised after assessing an individual’s long term risk for OA. One study found that a weight loss of 5% body weight over 30 months decreased the risk of incident radiographic knee OA(45); another study suggested that moderate exercise may be a “good treatment” for subjects at high risk for OA(46), and a meta-analysis showed that long term weight loss is increased when diet and physical activity are combined(47).…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage defects were scored from 0 to 6, and bone marrow edema patterns (BMEPs) were scored from 0 to 3 in the same six regions (patella, trochlea, medial femur, lateral femur, medial tibia, and lateral tibia). For each subscale (WORMS cartilage, meniscus, BMEP), a sum score was calculated by adding the scores of all subregions of each knee (37).…”
Section: Image Analysismentioning
confidence: 99%
“…Complete baseline and follow-up patellofemoral WORMS readings were available for the right knees of a sample of 443 of these potentially eligible subjects previously obtained by our group for several NIH-funded studies (Fig. 1) [22][23][24][25][26][27][28]. To minimize any potential influence caused by abnormalities of the extensor mechanism, and especially the quadriceps tendon in addition to inflammatory processes leading to effusion-synovitis, subjects showing these findings at baseline (extensor mechanism, n = 7; effusion-synovitis, n = 10) were excluded.…”
Section: Database and Subjectsmentioning
confidence: 99%